2009
DOI: 10.1038/ajh.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Hypertension Subtypes in Young and Middle-Age Adults

Abstract: The present results indicate that young-to-middle-age subjects with ISH have a smaller risk of developing ambulatory HT than either subjects with SDH or IDH. Whether antihypertensive treatment can be postponed for long periods of time in young subjects with mild elevations of clinic systolic BP and low global cardiovascular risk should be examined in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 30 publications
(39 reference statements)
4
20
0
1
Order By: Relevance
“…This high prevalence may be because our cohort included middle-aged adults who underwent only 1 BP measurement (23). Consistent with prior reports (1,2,4,5,22,24,25), those with ISH showed a higher proportion of current smoking, less education, higher BMI, higher heart rate, and higher serum total cholesterol levels compared with subjects with optimal-normal BP.…”
Section: Discussionsupporting
confidence: 89%
“…This high prevalence may be because our cohort included middle-aged adults who underwent only 1 BP measurement (23). Consistent with prior reports (1,2,4,5,22,24,25), those with ISH showed a higher proportion of current smoking, less education, higher BMI, higher heart rate, and higher serum total cholesterol levels compared with subjects with optimal-normal BP.…”
Section: Discussionsupporting
confidence: 89%
“…24 Elevated PP and ISH in youth are typical for the male sex as documented by several previous reports. 8,21,22,25 In the present study, we confirmed that high PP was more prevalent among the men than among the women especially in the younger age categories.…”
Section: Pathogenetic Considerationssupporting
confidence: 85%
“…Z jednej strony potwierdzono już wcześniej publikowane informacje, że większość młodych z IDH wykazuje tzw. fenotyp wazotoniczny, co oznacza niski CO z wysokim TPR, ale z drugiej strony ujawniono mniej znane mechanizmy rozwoju IDH dotyczące "fenotypu hiperkinetycznego" zależnego od zwiększonej SV serca [14,15]. U 37% osób z kohorty młodych pacjentów z nadciśnieniem granicznym opisano fenotyp hiperkinetycznego krążenia ze zwiększonym HR, SV i zwiększonym stężeniem noradrenaliny [16].…”
Section: Izolowane Nadciśnienie Rozkurczoweunclassified